Screening for medium-chain acyl CoA dehydrogenase deficiency: current perspectives - Soler-Alfonso C; Bennett MJ; Ficicioglu C (Dove Medical Press, 2016)
Claudia Soler-Alfonso,1 Michael J Bennett,2 Can Ficicioglu1 1Department of Pediatrics, Section of Metabolic Disease, 2Department of Pathology and Laboratory Medicine, The Children’s Hospital of Philadelphia and Perelman School of Medicine at the University of Pennsylvania, Philadelphia, PA, USA Abstract: Medium-chain acyl-CoA dehydrogenase (MCAD) deficiency is the most common disorder associated with fatty acid oxidation. The disorder is characterized by inability to generate sufficient energy from fatty acid metabolism during periods of catabolic stress caused by intercurrent illness or prolonged fasting. The metabolic consequences are severe and include hypoketotic hypoglycemia leading to a Reye-like hepatic encephalopathy syndrome and sudden death. If individuals are detected before a life-threatening episode, the complications of MCAD deficiency are preventable. Newborn metabolic screening enables the early detection of MCAD deficiency in many countries worldwide. The metabolic marker for MCAD deficiency “octanoylcarnitine” (C8) can be detected with a high degree of sensitivity in the newborns by tandem mass spectrometry. The 985A>G (K329E) mutation accounts for the majority of disease alleles, and approximately 47%–80% of MCAD patients are homozygotes for this mutation. Newborns homozygous for the 985A>G mutation have higher octanoylcarnitine levels than those who are heterozygous for 985A>G mutation or possess other genotypes. Time of sampling after birth and prematurity may affect the octanoylcarnitine levels in MCAD-deficient newborns. Tandem mass spectrometry newborn blood spot screening for MCAD deficiency is accurate and effective, and reduces morbidity and mortality in affected children. Keywords: MCAD, newborn screening, C8, octanoylcarnitine, tandem mass spectrometry, sudden death in childhood